A Preliminary Survey on the Security of Software-Defined Networks - Muhammet Fatih AKBAŞ; Enis KARAARSLAN; Cengiz GÜNGÖR (International Journal of Applied Methods in Electronics and Computers, 2016)
The number of devices connected to the Internet is increasing, data centers are growing continuously and computer networks are getting more complex. Traditional network management approach is becoming more difficult and insufficient. Software-Defined Networks (SDN) is a new generation networking approach which is expected to take place of the traditional computer networks. SDN architecture provides effective management of the large and complex networks. Although SDN have benefits from the network security perspective, it also brings new attack vectors. We believe that the network security problems in SDN architecture need more advanced solutions. In this work, a survey on the SDN security problems is presented, challenges are discussed. In this context, security threats and attack surfaces in SDN are described, the significant SDN security solution examples in the literature are given.